Association between minimally invasive surgery and late seizures in patients with intracerebral hemorrhage: A propensity score matching study - Lin, Jiahe; Lin, Ru; Li, Xianxian; Ye, Jiahe; Wang, Yuchen; Zhang, Beining; Chen, Xinling; Wang, Xinshi; Huang, Shanshan; Zhu, Suiqiang (Frontiers in Surgery, 2022)
Purpose: The association between minimally invasive surgery (MIS) for hematoma evacuation and late seizures after intracerebral hemorrhage (ICH) remains uncertain. We aimed to investigate whether MIS increases the risk of late seizures after ICH and identify the risk factors for late seizures in this patient subgroup. Methods: We retrospectively included consecutive inpatients diagnosed with ICH at two tertiary hospitals in China. The subjects were divided into the MIS group (ICH patients who received MIS) and medication group (ICH patients who received conservative medication). Propensity score matching was performed to balance possible risk factors for late seizures between the MIS and medication groups. Before and after matching, between-group comparisons of the incidence of late seizures were performed between the MIS and medication groups. Univariate and multivariate logistic regression analyses were used to identify independent risk factors for late seizures in MIS-treated patients. Results: A total of 241 and 1689 patients were eligible for the MIS and medication groups, respectively. After matching, 161 ICH patients from the MIS group were successfully matched with 161 ICH patients from the medication group (1:1). Significant differences (p<0.001) were found between the MIS group (31/241, 12.9%) and medication group (69/1689, 4.1%) in the incidence of late seizures before matching. However, after matching, no significant differences (p=0.854) were found between the MIS group (17/161, 10.6%) and medication group (16/161, 9.9%). Multivariate logistic regression analysis revealed that cortical involvement (OR=2.547; 95% CI=1.137-5.705; p value=0.023) and National Institutes of Health Stroke Scale (NIHSS) scores (OR=1.050; 95% CI=1.008-1.094; p value=0.019) were independent risk factors for late seizures. Conclusion: Our study revealed that receiving MIS did not increase the incidence of late seizures after ICH. Additionally, cortical involvement and NIHSS scores were independent risk factors for late seizures in MIS-treated patients.